GAMBARAN KADAR KADMIUM (Cd) PADA PEROKOK AKTIF PEKERJA KURIR SERVIS - Purwati -; Yuli Budi Hastuti (LPPM Universitas Abdurrab, 2025)
Smoking activities, especially tobacco, produce ash, light and smoke that contain toxins for the body. The largest exposure to toxins from smoking is Cadmium (Cd), around 25% - 50% of Cd is absorbed through cigarette smoke. Cd will enter the respiratory tract in the form of Cadmium Oxide (CdO) then to the lungs and bind to erythrocytes, following the blood circulation to the tissues and organs of the body. The aim of this study was to determine the levels of cadmium in the blood of active smokers and used a descriptive method. The samples used came from 15 subjects who were willing to have blood samples taken. The examination method used is ICP MS The results of the study from 15 samples of active smokers who were courier service workers showed that the highest level of cadmium (Cd) was 3.1 µg / L and the lowest cadmium (Cd) content was 0.3 µg / L. The results of the study of 15 samples of active smokers who are courier service workers found that cadmium (Cd) levels ranged from 3.1 µg/L to 0.3 µg/L. The conclusion of this study is that cadmium (Cd) levels in the blood are still within normal limits, namely below 5.0 µg/L according to OHSA (Ocupational Safety and Health Administration).